"Trenirke" in "oranžne face" - "vidiš ga pa veš" - Bajič, Blaž (Etnolog. Nova vrsta (Ljubljana), 2012)
The knowledge of the students in Ljubljana about the external image appearanceof čefurji has a neat, socially constructed form and content, and this means that we are dealing with a Foucauldian discourse. A first glance, the innocent and amusing descriptions of the clothes, fashion accessories, andbehaviour of čefurji are merely a superficial aspect of the discourse aboutthe čefur as the ŽOtherŽ, whose differs from ŽUsŽ in an unbridgeable way.This difference is seen by the subjects of the discourse as a consequence of the individual's decision to belong to the čefur subculture, suggesting that their exclusion is their own choice. But if we consider the socio-historical context, we find that the discourse about the čefurji is partof the Slovene nationalist discourse about ŽjužnjakiŽ (southerners, pejorative expression), and as such one the mechanisms of exclusion.
Keywords: ethnology; etnologija; ljudsko življenje; Slovenci; Slovenes; subculture; subkultura; priseljenci; čefurji; zunanja podoba